2023
DOI: 10.1098/rsif.2022.0555
|View full text |Cite
|
Sign up to set email alerts
|

Social stratification in networks: insights from co-authorship networks

Abstract: It has been observed that real-world social networks often exhibit stratification along economic or other lines, with consequences for class mobility and access to opportunities. With the rise in human interaction data and extensive use of online social networks, the structure of social networks (representing connections between individuals) can be used for measuring stratification. However, although stratification has been studied extensively in the social sciences, there is no single, generally applicable me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…For instance, influence can be categorized differently based on the subject and audience, such as personal influence [28] and social influence. If we differentiate influence based on the online and offline realms, we can divide it into digital influence [29] and real-world influence. In the digital society, personal influence is often reflected through metrics like follower count, likes, and comments.…”
Section: Perspectives On Influence Within the Scientific Social Strat...mentioning
confidence: 99%
“…For instance, influence can be categorized differently based on the subject and audience, such as personal influence [28] and social influence. If we differentiate influence based on the online and offline realms, we can divide it into digital influence [29] and real-world influence. In the digital society, personal influence is often reflected through metrics like follower count, likes, and comments.…”
Section: Perspectives On Influence Within the Scientific Social Strat...mentioning
confidence: 99%
“…Social stratification refers to the hierarchical ranking of individuals and groups within a society based on factors such as income, education, and social status [2,3]. Research has shown that social stratification can influence the recommendations that users receive from recommender systems [4].…”
Section: Introductionmentioning
confidence: 99%